Odpowiedzi

2010-01-04T20:18:21+01:00
X-y=3
-5x+10y=-10 x=4 y=1

4-1=3
-5*4+10*1=-10

4-1=3
-20+10=-10

x-2y=-4
0,5x+y=2 x=0 y=2

0-2*2=-4
0.5*0+2=2
2010-01-04T20:19:13+01:00
X-y=3|*10
-5x+10y=-10

10x - 10y = 30
-5x + 10y = -10

dodajemy to

10 x - 10 y - 5x +10y = 20
5x = 20
x = 4

podkładamy

40 - 10 y = 30
-40+30= 10 y
10y = 10
y= 1

x=4 y=1
Najlepsza Odpowiedź!
2010-01-04T20:25:09+01:00
X-y=3
-5x+10y=-10

x-y = 3 / *5
-5x + 10y = -10

5x - 5y = 15
-5x +10y = -10

5x - 5y + (-5x) + 10y = 15 - 10
5y = 5 / :5
y =1

x-y = 3
x=3+1
y = 4

---------------------------------
x - 2y =-4
0,5x + y = 2 / * 2

x-2y= -4
x + 2y = 4

x - 2y + x + 2y = 4 - 4
x = 0

x + 2y = 4
0 + 2y = 4
2y = 4 / :2
y = 2